Effect of Thalassia Testudinum Flour on the Growth and Production of Polyphenols of Phaseolus Vulgaris - Jesus, Mex-Alvarez Rafael Manuel de; Magali, Guillen-Morales Maria; Margarita, Garma-Quen Patricia; David, Yanez-Nava; Enrique, Chan-Martínez Roger; Antonio, Uc-Guerra Jorge (Journal of Posthumanism, 2025)
Remains of Thalassia testudinum abound and accumulate on the coasts of Campeche and represent a pollution problem when decomposing; However, the biomass of this marine plant is rich in biomolecules, both primary metabolites (proteins, carbohydrates and lipids) and secondary (polyphenols), which can be used to nourish crops as a biofertilizer. Therefore, the objective of this work was to evaluate the effect of the dust obtained from the drying and grinding of Thalassia testudinum collected on the beaches of San Francisco de Campeche on the germination and growth of Phaseolus vulgaris. The P. vulgaris seeds were placed in individual wells of 20 mL of 0.5% agar-agar, the control only contained the seeds and the problem groups were placed in each well with 10, 30 and 100 mg of dry sargassum powder in the agar after boiling, when cooled to 40ºC; The vials were placed in a humid chamber for 7 days for germination and growth. At the end of the period, the seedlings were harvested and their morphometry was measured (size, root size and weight of the plant) and the content of pigments and polyphenols were determined. and the antioxidant activity of methanolic extracts from the leaves of harvested plants. The results obtained demonstrate an increase in the growth of P. vulgaris treated with T. testudinum, which is why it is recommended to continue the study to evaluate its potential as a biofertilizer.